ASIMETRI TRANSMISI HARGA EKSPOR KOPI INDONESIA KE NEGARA IMPORTIR UTAMA - Purwadi Purwadi; Sri Widodo; Masyhuri Masyhuri; Djuwari Djuwari (Jurnal Dinamika Sosial Ekonomi, 2005)
This paper aims to examines the relationships of prices between Indonesia and major importer countries. The causality are analysed by Granger Causality used first-differenced data because all series first-differenced stasionary. To analyze the asymmetry of price transmission by error corection model approach. Causality estimeting show that the direction was from Indonesia to major importing countries, USA, Germany, and Japan and no reverse. The Conclusion is that the price transmission of relatonship between Indonesia Coffee prices and coffe prices in USA, Germany and Japan was assymetry adjustment, the falling price was slower than the raising price, but the accumulation adjustment at the falling price was greather than the raising price.Keywords: Price asymmetry, major importing countries, causality, speed adjustment